(untitled) (Research, Society and Development, 2022)
The Brazilian Northeast stands out, among other things, for its fruit production and the availability of solar energy. However, the production of dried fruit in this region of the country is still not expressive. Studies on food drying have been developed around the world, since the traditional drying process in an oven requires large investments and high electricity consumption, increasing the cost of the final product. Solar drying in equipment built with low-cost materials and whose operation and maintenance can be performed without the need for highly complex actions, becomes an appropriate technology for family farming. The objective of this work was to compare the performance of an indirect exposure solar dryer in different climates and meteorological conditions. For that, experimental drying tests were carried out, in the drying of silver bananas, in the cities of Campina Grande, PB and Pombal, PB, in periods of greater and lesser intensity of solar radiation. It was possible to observe the influence of the temperature and relative humidity conditions of the ambient air and the incidence of solar radiation on the drying time. Average thermal yield of 30,04% and average drying time of 13,5 hours were obtained, results similar to those reported in the literature.